2020
DOI: 10.3389/fpsyg.2020.00734
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ant Foraging: A Review of the Role of Information Use and Personality

Abstract: Animals live in heterogeneous environments where food resources are transient and have to be exploited rapidly. Ants show a wide range of foraging strategies and this activity is tightly regulated irrespective of the mode of recruitment used. Individual foragers base their decision to forage on information received from nestmates (social information). Transmission of information can be in the form of direct physical interactions such as antennation or indirect exchange of information such as laying of pheromon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 79 publications
0
23
0
1
Order By: Relevance
“…Scouts form a distinct caste in honey bees, which search out new food sources even when food is plentiful (Beekman et al ., 2007). The term scout in ants, however, is used loosely to refer to individuals which go out in search of resources (de Biseau & Pasteels, 1994; Robson & Traniello, 2002; Lanan, 2014; Kolay et al ., 2020). Specialist trail followers, used to re‐establish old trails, have been reported (Jackson et al ., 2006; Evison et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scouts form a distinct caste in honey bees, which search out new food sources even when food is plentiful (Beekman et al ., 2007). The term scout in ants, however, is used loosely to refer to individuals which go out in search of resources (de Biseau & Pasteels, 1994; Robson & Traniello, 2002; Lanan, 2014; Kolay et al ., 2020). Specialist trail followers, used to re‐establish old trails, have been reported (Jackson et al ., 2006; Evison et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…While classical models of collective behaviour downplay individual differences between workers, both transient and long‐lasting individual specialisation are common components of collective behaviours such as house hunting and prey retrieval (Robson & Traniello, 1999, 2002; Fonio et al ., 2016). While several studies have examined the consistency of individual ant behaviours such as exploration or aggression (Kolay et al ., 2020), none have examined consistency in pheromone following versus ignoring pheromone trails.…”
Section: Introductionmentioning
confidence: 99%
“…One of the largely studied social decision mechanisms in ants is mass recruitment ( Kolay et al, 2020 ; Reznikova, 2020 ). The decision between alternative foraging patches in mass recruitment results from the conditional amplification of individual scent signals during mass recruitment: the first finder marks the trail with pheromone in her way back to the nest, thus recruiting others to the foraging patch, but in many species, the recruited foragers also strengthen the first trail markings only in their way back to the nest, i.e., after evaluating by themselves the foraging patch ( Beckers et al, 1992a ; Mailleux et al, 2003 ).…”
Section: Information Network Within Social Insectsmentioning
confidence: 99%
“…Although the existence of these regulatory constraints is possible, the very decentralized nature of colony organization, relying heavily on anonymous agents using local information and indirect interactions ( Feinerman and Korman, 2017 ), seems to reduce the possibility of regulation through supplementary social structures. There is certainly regulation of interactions by individuals ( Kolay et al, 2020 ). For example, Monomorium ants produce a volatile pheromone that repels workers from unprofitable resources ( Robinson et al, 2005 ), thus contributing, for example, to the decline of an established trail.…”
Section: Application Of the Organizational Approach To Socialitymentioning
confidence: 99%
“…Therefore, being guided by cues or signals left by other individuals can help reduce costs related to foraging. In the last years, a series of studies have been shown the use of social information during the exploitation and selection of resources in eusocial insects (Czaczkes et al., 2015), mainly in ants (Kolay et al., 2020; Stroeymeyt et al., 2017) and bees (Dunlap et al., 2016; Grüter & Farina, 2009; Wray et al., 2011). For termites, however, studies on the use of social information during resource selection are still scarce.…”
Section: Introductionmentioning
confidence: 99%